Pengaruh Motivasi dan Pelatihan Kerja Terhadap Kinerja Karyawan pada PT OSI Electronics Indonesia Batam - Rina Desika Nainggolan; Hikmah Hikmah (eCo-Buss, 2022)
Human undoubtly still one of the most important source that company should be aware of, therefore to find out what things that impactful on performance is a must. The method used were using test of validity, reliable test, normal test, multicolinearity test, heterocedasticity test, multiple liniar regresion analytict, coeficient of determination analytic, t test and F test by using the help of software SPSS 26 . Data collected by using the answer of questioner that spread to to 150 respondant. This test obtained a calculated f value of 31.558, with table F the magnitude is 3.06. In this test, the relationship of all variables which are motivation and job training are both giving impact. This statement is supported by the calculated F which is higher than the F table, and the significant value is 0.000 which is fewer than 0.05. and it come to a conlusion that motivation and job training affect work performance of OSI Electronics employees